2022
DOI: 10.1016/j.clnu.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in critically ill COVID-19 ARDS patients

Abstract: Background & Aims Vitamin D’s pleiotropic effects include immune modulation, and its supplementation has been shown to prevent respiratory tract infections. The effectivity of vitamin D as a therapeutic intervention in critical illness remains less defined. The current study analyzed clinical and immunologic effects of vitamin D levels in patients suffering from coronavirus disease 2019 (COVID-19) induced acute respiratory distress syndrome (ARDS). Methods This was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
2
26
0
6
Order By: Relevance
“…On the contrary, no difference was observed in the vitamin D levels of those hospitalized and those admitted to the ICU, and furthermore, among the ICU patients, there were no significant differences in ICU clinical outcomes between patients with low and normal vitamin D levels [ 103 ]. Similar results were observed in another study, in which 96% of critically ill COVID-19 ARDS patients exhibited vitamin D deficiency; however, the low levels of 25(OH)D were not related to changes in clinical course, whereas the low levels of 1,25(OH)D were associated with prolonged mechanical ventilation [ 104 ].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…On the contrary, no difference was observed in the vitamin D levels of those hospitalized and those admitted to the ICU, and furthermore, among the ICU patients, there were no significant differences in ICU clinical outcomes between patients with low and normal vitamin D levels [ 103 ]. Similar results were observed in another study, in which 96% of critically ill COVID-19 ARDS patients exhibited vitamin D deficiency; however, the low levels of 25(OH)D were not related to changes in clinical course, whereas the low levels of 1,25(OH)D were associated with prolonged mechanical ventilation [ 104 ].…”
Section: Introductionsupporting
confidence: 86%
“… Cut-off for vitamin D Patient cohort Outcome/Findings Reference <30 ng/mL 154 patients: 91 asymptomatic COVID-19 patients and 63 severely ill patients requiring ICU admission Vitamin D level is markedly low in severe COVID-19 patients [ 94 ] <10 ng/mL 42 patients with acute respiratory failure due to COVID-19, treated in Respiratory Intermediate Care Unit (RICU) Patients with severe vitamin D deficiency had a 50% mortality probability [ 96 ] <15.2 ng/mL 30 critically ill COVID-19 patients The low vitamin D group had an increased risk of 28-day ICU mortality [ 97 ] <50 nmol/L 50 patients admitted to the ICU No significant differences in ICU clinical outcomes (invasive and non-invasive mechanical ventilation, acute kidney injury and mechanical ventilation and hospital days) between patients with low and normal vitamin D levels [ 103 ] <30 ng/mL 26 critically ill COVID-19 ARDS patients 96% of critically ill COVID-19 ARDS patients suffered from vitamin D deficiency. Low vitamin D levels were not related to changes in clinical course [ 104 ] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recently, a systematic review and meta-analysis indicated that low vitamin D status might be associated with an increased risk of COVID-19 infection [23]. Low vitamin D was also reported in critically ill COVID-19 ARDS patients, in which even the active form 1,25-dihydroxyvitamin D was found to be low [24]. This biochemical form mediates most of the endocrine effects of vitamin D, including immune-modulatory functions [25,26].…”
Section: Discussionmentioning
confidence: 99%